Factors affecting hematological parameters in Creole goats on the Southern Coast of Peru - Jhony Soca; Emmanuel Alexander Sessarego; Pamela Sarmiento; María José Cevallos-Cardenas; Juan Canchino-Gutierrez; Jose Teran; Jose Antonio Ruiz; Juancarlos Cruz-Luis; Danny Julio Cruz (Veterinary World)
Background and Aim: Hematological parameters are critical indicators of health and physiological status in goats. This study aimed to evaluate the effects of location, feeding regimen, age, and body condition score (BCS) on hematological parameters in Creole goats reared under extensive systems on the southern coast of Peru and to establish context-specific reference values.